Content normalization of the dissolved oxygen in waste waters entering in water bodies - Проскурнин, Олег Аскольдович (Technology audit and production reserves, 2015)
The scientific and legal demand for composition normalization of the wastewater discharged into water bodies (in particular in the natural waterways) in order to prevent environmental contamination above accepted level are grounded in the article. The existing methodological approaches to determining the permissible wastewater composition are considered. It is noted that these approaches are not applicable to the calculation of permissible content of dissolved oxygen. It is proposed to define the minimum acceptable oxygen content in wastewater by solving the optimization problem. Optimization criterion is the maximum permissible anthropogenic impact on the ecosystem. The problem is considered for a watercourse. It is proposed the full dilution of sewage water of a water body. It is given an example of the calculation for the two issues, showing performance of the proposed method. The given research aimed at improving the valuation methodology of wastewater disposal.